PENDAMPINGAN BANK SAMPAH SIMPATIK PROJECT MELALUI PENINGKATAN PRODUKTIVITAS DAN PEMASARAN ONLINE DI NAGORI SAIT BUTTU SARIBU KECAMATAN PAMATANG SIDAMANIK - Tioner Purba; Elfina Okto Posmaida Damanik; Rolando Sihombing; Eko Agus Suyono; Irkham Widiyono; Djarot Heru Santosa; Jhonson Allen Marbun; Corry Corry (Jurnal Abdimas Bina Bangsa, 2023)
Nagori Sait Buttu is one of the tourist villages in Simalungun Regency, which offers natural beauty and agro-tourism. The problem faced in developing tourism in Sait buttu is waste management. The Simpatik Project Garbage Bank has been established for a long time, but its activities are only collecting waste and selling it. Through this community service, the community is trained to process the collected waste, namely organic waste and inorganic waste. Organic waste is processed into several products such as food and compost, while inorganic waste is processed into various crafts. Products are marketed online and offline. Communities are trained to market their products online by opening a shop on the Shopee application. Financial bookkeeping training was also carried out with the Android cashbook application. Currently, the Sympathetic Project Waste Bank already has various processed waste products that are marketed through Shopee and is able to record finances with the Android cashbook application. Through this service, the community through a sympathetic waste bank benefits by increasing income. Through the activities of the Sympathetic Waste Bank project, the environment is getting cleaner